A novel air source heat pump powered bed-based space heating (ASHP-BBSH) system for improved indoor thermal environment. (February 2019) - Fang, Guanyu; Chen, Wenjing; Wang, Caixia; Chan, Ming-yin; Deng, Shiming; Liu, Xuefeng; Yan, Huaxia
Abstract: A novel air source heat pump powered bed-based space radiation heating (ASHP-BBSH) system is reported in this paper. This novel system combines the merits from a Chinese Kang, or a heated bed, widely used in northern rural China and a standard ASHP system, which can provide localized space heating via both convection and radiation to maintain a comfortable indoor thermal environment, at reduced energy use. In this novel bed-based system, a bed is heated and thus used as a radiator for providing space heating at both daytime and nighttime. In this paper, firstly, there is an introduction to the novel ASHP-BBSH system. Secondly, based on the experiment setup dimensions, a numerical model is built with a real size thermal manikin. Thirdly, the thermal environment generated by the ASHP-BBSH system is analysed by Fluent. The numerical results show that the ASHP system can achieve a uniform thermal environment and energy saving potential.